2018
DOI: 10.1177/1082013218802027
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated sour cherry pomace extract: Effect on the colour and rheology of cookie dough

Abstract: In this study, the effect of encapsulated sour cherry pomace extract on the physical characteristics of the cookie dough (colour, textural and rheological properties) was investigated. Sour cherry pomace extract encapsulated in whey (WE) and soy proteins (SE) was incorporated in cookie dough, replacing 10% (WE10 and SE10) and 15% (WE15 and SE15) of wheat flour. The dough samples containing encapsulates had the grey-blue colour ( b* values significantly decreased compared to control sample). Due to the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…It has been reported that biscuit dough usually contains more sugar and fat, while the moisture level remains low. For this reason, shortening agents should be used in a solid/semisolid state to ease the processing of the dough at room temperature. , As a result, the final moisture level of the dough can directly affect the firmness of the dough and the ingredients’ ability to bind with water . The moisture content of the control and the oleogel-added dough are represented as a bar graph in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that biscuit dough usually contains more sugar and fat, while the moisture level remains low. For this reason, shortening agents should be used in a solid/semisolid state to ease the processing of the dough at room temperature. , As a result, the final moisture level of the dough can directly affect the firmness of the dough and the ingredients’ ability to bind with water . The moisture content of the control and the oleogel-added dough are represented as a bar graph in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 As a result, the final moisture level of the dough can directly affect the firmness of the dough and the ingredients' ability to bind with water. 36 The moisture content of the control and the oleogel-added dough are represented as a bar graph in Figure 1b. OG0 dough, which contained only butter as the shortening agent, had a moisture content of 25.6%.…”
Section: Effect Of Oleogel Substitution On the Visualmentioning
confidence: 99%
“…As in milk, microencapsulation helps maintain stable health compounds, such as anthocyanins, even after a thermal process, such as cookie baking [ 71 ]. Such is the case regarding the incorporation of microcapsules of sour cherry pomace extract in whey protein, which prevents the loss of anthocyanins due to processing and preserves the antioxidant capacity of the extract in the product [ 72 ].…”
Section: Microcapsules In Functional Foodsmentioning
confidence: 99%
“…The addition of microcapsules with sour cherry pomace extract in whey protein modifies the final texture of cookies, increasing the softness (by 43%) and red color (by 1400%), which could serve to color a strawberry cookie, or when a pink color is desired without using extra synthetic or natural dyes, and reduces the brightness by 33% [ 71 ].…”
Section: Application Of Microcapsules For Sensory Improvementmentioning
confidence: 99%
“…The enrichment of snack foods with sour cherry is innovative and has not been extensively studied, except in the form of encapsulation. Petrovic et al [ 20 ] encapsulated sour-cherry-pomace extract in soy and whey protein carriers in the preparation of cookie dough and showed a significant increase in anthocyanin content, which subsequently caused the change in cookie dough color. Gumul et al [ 21 ] also enriched GF breads with encapsulation of 10% and 20% sour-cherry-pomace in extruded rice flour preparations, successfully increasing the bioactive compound content of GF bread and delaying bread crumb hardness.…”
Section: Introductionmentioning
confidence: 99%